2020
DOI: 10.1177/1098612x20961350
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of copper accumulation in archived liver specimens from cats

Abstract: Objectives The aim of this study was to assess hepatic copper concentrations and zonal distribution in cat liver specimens. Methods For this study, 121 archived, formalin-fixed, paraffin-embedded liver specimens from cats were used. Tissue sections were stained for copper with rhodanine and scored from 0 (no copper accumulation) to 5 (panlobular copper accumulation). The tissue specimens were then deparaffinized and hepatic copper concentrations were measured using flame atomic absorption spectroscopy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…Previous studies of hepatic copper concentrations in cats found a wide range of hepatic copper concentrations in healthy control cats and cats without hepatobiliary diseases (e.g., 9.5–451.6 μg/g dry weight liver in 23 cats and 10.8–394.8 μg/g dry weight liver in 47 cats) [ 30 , 31 ]. We previously found copper concentrations greater than the ULRI in cat liver tissue submitted to a US-based veterinary laboratory even when hepatic lesions were not appreciated [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of hepatic copper concentrations in cats found a wide range of hepatic copper concentrations in healthy control cats and cats without hepatobiliary diseases (e.g., 9.5–451.6 μg/g dry weight liver in 23 cats and 10.8–394.8 μg/g dry weight liver in 47 cats) [ 30 , 31 ]. We previously found copper concentrations greater than the ULRI in cat liver tissue submitted to a US-based veterinary laboratory even when hepatic lesions were not appreciated [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections were stained with hematoxylin and eosin (H&E) for histopathological analysis. Tissue specimens were classified based on previously published criteria of inflammation, lipid accumulation, and the presence of neoplastic cells [ 15 ]. The scoring system and classification criteria are described in S1 and S2 Tables.…”
Section: Methodsmentioning
confidence: 99%
“…[30][31][32][33] Similar to dogs, 7 Cu can accumulate in the tissue of cats, especially the kidney and liver. 3,4 In addition, the amount of dietary Cu correlated with tissue concentrations in cats and concentrations in the liver of cats reflect dietary intake. 6,34 Therefore, the lack of defined maximum regulatory standards in commercial cat foods raises concern for potentially high dietary intakes with consequential accumulation of these trace minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high intake can reduce bioavailability of other nutrients (eg, Zn interferes with Cu absorption) or might lead to accumulation in tissues of cats, especially the kidney and liver. 36…”
Section: Introductionmentioning
confidence: 99%
“…Copper-induced chronic hepatitis in a European short was presented a decade later [112] (Meertens 2005). The levels of copper, and some other trace elements in feline livers were described by various groups [113][114][115][116] (Andreani 2010; Whittemore 2012; Passlack 2014; Yamkate 2020). In addition to house cats (Felis catus), copper levels in other felidae were measured, including bobcats, tigers, cougars, coyotes, and lions [117][118][119] (Bernard 2015; Thomason 2016), Hough 2020.…”
Section: Dogs and Cats Are Clearly Different With Regard To Hepatic C...mentioning
confidence: 99%